Cashless Society Phenomenon in Jakarta City's use of The Digital Wallet "DANA" as A Payment Tool - Jatmika, Surya; Purboningrum, Vivi; Harsono, H; Hidayat, Muhamad Taufik (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: The change in society from cash payments to cashless payments in various aspects of life is called the cashless society phenomenon. Citizens are starting to use various cashless payment methods, starting from cards or digital wallets. One of the digital wallets in Indonesia that provides various payment services is DANA. The aims of this research were (1) to describe the cashless society phenomenon in South Jakarta City, (2) to describe the use of the DANA digital wallet as a post-pandemic payment tool in South Jakarta City, and (3) to identify obstacles to using the DANA digital wallet in South Jakarta City. Methodology: This research applied qualitative research with a phenomenological research design. The subjects of this research consisted of nine sources with the criteria involving three teenagers aged 16-18 years, three teenagers aged 18-25 years, and three young families whose members aged 20-35 years. The data collection techniques in this research involved interviews, observation, and documentation. This research employed interactive data analysis techniques. Results: The results of the research show that (1) the cashless society phenomenon in the citizens of South Jakarta City tends to be dominated by online shopping activities via e-commerce, (2) the reason the citizens of South Jakarta City use the DANA application compared to other applications is that the DANA application is easy to use. Apart from that, the use of the DANA digital wallet application by merchants who have collaborated with the application tends to be used for purchasing credit and internet data as well as money transfer transactions (3), and problems with using the DANA application occur for several application users, such as problems with errors in the application which cause transaction disruption occurs so that the transaction fails. Even so, this is no different from other digital wallets.